Brief History of Conscientization Category and why Paulo Freire Abandoned It - Stańczyk, Piotr (INSTED: Interdisciplinary Studies in Education & Society, 2018)
This article is focusing on the crucial, for emancipatory pedagogy of P. Freire, category of conscientizaç?o. On the one hand this notion was the core part of Freirean philosophy of education, on the other, there was some important reasons of abandoning this category by P. Freire. In P. Freire?s opinion conscientizaç?o was overused or used in naive or even reactionary way. To reconstruct P. Freire?s reasons to abandon conscientizaç?o category this article contains analysis of two Freire?s text which delimit boundary between use and abandonment of this notion. The context of this article are hegemony of neoliberal discourse in education, knowledge-based society and economy and also appreciation of popular classes in educational emancipatory process.